Knowledge, attitude, and practice of providing first aid by commercial motorcyclists: a cross-sectional study - Ufashingabire Minani, Christine; Soh, Kim Lam; Abdul Manaf, Rosliza; KC Mani, Kulanthayan; Twagirumugabe, Theogene (Cambridge University Press, 2024)
Introduction: The mortality and morbidity due to road traffic crashes (RTCs) are increasing drastically world-wide. Poor prehospital care management contributes to dismal patient outcomes, especially in low- and middle-income countries (LMICs). This study aimed to assess the knowledge, attitude, and self-reported practice (KAP) of providing first aid for RTC victims by commercial motorcyclists. In addition, it determined the relationship between sociodemographic characteristics and the level of KAP, then the predicting factors of outcome variables. Methods: A cross-sectional study of 200 randomly selected commercial motorcyclists was conducted in May 2021. A chi-square test and multivariate analysis were used to analyze data. Results: The findings showed that most participants had a poor knowledge level (87.5 %), positive attitudes (74.5%), and poor self-reported practice (51.5%). Previous first-aid training and knowing an emergency call number for the police were predictors of good knowledge (AOR = 3.7064; 95% CI, 1.379-9.956 and AOR = 6.132; 95% CI,1.735-21.669, respectively). Previous first-aid training was also a predictor of positive attitudes (AOR = 3.087; 95% CI, 1.033-9.225). Moreover, the likelihood of having an excellent self-reported practice was less among participants under 40 years of age (AOR = 0.404; 95% CI, 0.182-0.897) and those who cared for up to five victims (AOR = 0.523; 95% CI, 0.282-0.969). Contrary, previous first-aid training (AOR = 2.410; 95% CI, 1.056-5.499) and educational level from high school and above increased the odds of having good self-reported practice (AOR = 2.533; 95% CI, 1.260-5.092). Conclusion: Considering the study findings, training should be provided to improve the knowledge and skills of commercial motorcyclists since they are among the primary road users in Rwanda and involved in RTCs.